Utilization of Medicinal Plants to Overcome Diabetes in Nagari Manggopoh Subdistrict Lubuk Basung Regency of Agam - Annisa Tulhasanah; Moralita Chatri; Resti Fevria; Des M (Universitas Negeri Padang, 2020)
The use of medicinal plant media is done to overcome Diabetes Mellitus which is expected to prevent complications, lower blood sugar and repair damaged cells in the body. Public knowledge about the use of medicinal plants has become a cultural heritage in Indonesia to date, such as in Nagari Manggopoh. This research was conducted in Nagari Manggopoh, Lubuk Basung Subdistrict, Agam Regency in December 2019 until January 2020. The method used is descriptive survey approach. The results found that in Nagari Manggopoh found 9 species of medicinal plants used to treat diabetes, which came from 8 families. The most commonly found plants are from the Asteraceae family of 2 species. Of the 9 species of 5 species have been cultivated in the homes of residents, and 3 species grow wild in the yard and in the forest.